Promising rootstocks alternative to ’Rangpur’ lime in the Coastal Tablelands of the state of Sergipe, Brazil - Carvalho, Luciana Marques de; Carvalho, Hélio Wilson Lemos de; Soares Filho, Walter dos Santos; Martins, Carlos Roberto; Passos, Orlando Sampaio (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to identify alternative rootstocks to ’Rangpur’ lime, for production of ’Pêra’ orange, under the conditions of the Coastal Tablelands of the state of Sergipe, Brazil. Forty‑three rootstocks were evaluated for plant height, canopy, photosynthetic rate, proline content, productive efficiency, yield, and productivity. The ’Rangpur’ common lime was considered as standard. The rootstocks TSKC x (LCR x TR) ‑ 059 hybrid, ’Riverside’ citrandarin, ’Rangpur CNPMF ‑ 03’ lime, and other 12 exceeded ’Rangpur’ common lime in inducing crown production efficiency; ’Red Rough’ lime, ’Indio’ citrandarin, and other four promoted greater productivity; TSKC x CTRK ‑ 001 and TSKFL x CTC13 ‑ 012 stood out for magnitude of CO2 assimilation; and TSKC x (LCR x TR) ‑ 040 and TSKC x CTRK ‑ 001 showed higher proline accumulation. The following rootstocks are considered promising alternatives: TSKC x (LCR x TR) - 059 hybrid; ’Indio’, ’Riverside’, and ’San Diego’ citrandarins; ’Rugoso Vermelho’ and ’Rangpur CNPMF ‑ 03’ limes; and TSKC x CTRK ‑ 001, TSKFL x CTC13 ‑ 012, TSKC x (LCR x TR) ‑ 040, TSKC x LHA ‑ 006, TSKC x CTQT1434 ‑ 001, TSKC x CTSW ‑ 058, and TSKFL x CTARG ‑ 028 hybrids.